(untitled) (Educação e Pesquisa, 1999)
Based on the hypothesis that there is an inevitable linking in Gramscis thought involving historical knowledge, political praxis, cultural struggle, and human development this paper tries to make explicit Gramscis reflection on the development of man in society as an intrinsic part of his political theory. In order to reveal the pertinence of this angle in the reading of Gramscis work this paper will attempt to expound and interpret his ideas in view of a historicist methodological procedure which, it is assumed, makes it possible to place theoretical problems - the ideas produced in the past - within the specific contexts where they were born. The conclusions draw attention to an issue that is potentially relevant to the Gramscian perspective: the possibility of building a theory of human development, based on Gramsci, that avoids reducing the understanding of the development process to the intellectual development of man conceived in isolation while at the same time avoids escaping the extreme opposite of seeing the development of personality in an excessively deterministic manner, and man as a passive product of his social environment. Gramsci regards the issue of the development of the individual as a strategic function of politics for the implementation of the project of a class to become hegemonic. He thinks this is the task of a vanguard with respect to the political activists, as well as a responsibility of the elders to the younger generation in the perspective of creating more advanced forms of civility.